The Effect of Government Information Technology Utilization (E-Government), Human Resource Capacity, and the Government Internal Control System (SPIP) on the Accountability of Regional Financial Management - Indarsi; Baihaqi; E. Novita Sari (Indonesian Journal Economic Review (IJER), 2026)
Regional financial management accountability is a fundamental principle of good governance. Despite the Central Bengkulu Regency Government consistently receiving an Unqualified Opinion (WTP) on its financial statements, audit findings from the Audit Board of the Republic of Indonesia (BPK) continue to reveal weaknesses in financial management and internal control. This situation indicates that a favorable audit opinion does not necessarily reflect optimal financial accountability, underscoring the need to examine the factors influencing regional financial management accountability. This study aims to analyze the effects of government information technology utilization (e-government), human resource capacity, and the Government Internal Control System (SPIP) on regional financial management accountability in the Regional Apparatus Work Units (SKPD) of Central Bengkulu Regency. A quantitative approach was employed using a census (total sampling) technique involving all 40 SKPD, represented by 40 Financial Management Officers (PPK-SKPD). Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics. The results indicate that human resource capacity and the Government Internal Control System (SPIP) have a positive and significant effect on regional financial management accountability, whereas the utilization of e-government has no significant effect. These findings provide empirical support for Stewardship Theory, emphasizing that competent human resources and effective internal control systems play a more substantial role in enhancing financial accountability than technology utilization alone. The findings also imply that local governments should prioritize strengthening employee competence and improving the effectiveness of SPIP while optimizing the implementation of e-government to achieve better regional financial management accountability.